90.2k views
23 votes
Can someone explain how to get the answer I’m confused on how to solve

Can someone explain how to get the answer I’m confused on how to solve-example-1

2 Answers

7 votes

Answer:

x = 29

(x + 3)° = 32°

(x - 1)° = 28°

(x + 1)° = 30°

Explanation:

  • (x + 3)° + (x - 1)° + (x + 1)° = 90°

  • -> (x + x + x +3 -1 + 1)° = 90°

  • -> (3x + 3)° = 90°

  • -> 3x + 3= 90

  • -> 3x = 90 - 3

  • -> 3x = 87

  • -> x = 87/3

  • -> x = 29

  • -> (x + 3)° = (29 + 3)° = 32°

  • -> (x - 1)° = (29 - 1)° = 28°

  • -> (x + 1)° = (29 + 1)° = 30°
User Martel
by
4.9k points
11 votes

Answer:

x=29

Explanation:

The square notation indicates 90 degrees.

90=(x+3)+(x-1)+(x+1)

90=3x+3

87=3x

x=29

User Jounathaen
by
5.0k points